A Qualitative Analysis of the Educational Value of Commercial Video Games - Salvador Reyes-; Carlos Ramírez-Moreno; Jose María Barroso-Tristán (MDPI AG, 2022)
Video games have evolved from a mere object of consumption to a cultural artifact of our time. Each cultural milieu is connected to the dominant technologies of its time, and video games today present narratives that allow for meaningful dialogues between the younger generations and the themes or content they find interesting. The main objective of this research was to highlight the value of commercial video games with an ideal potential for transmitting pedagogical and curricular content in educational contexts. The scientific methodology used in this study followed a mixed approach divided into three stages (qualitative-qualitative-quantitative). The wide variety of themes and settings found among the 75 top-rated games on the Steam digital distribution platform sheds light on the interests of young people, representing a broad and rich range that highlights their interest in topics that are close and relevant to them. Video games can no longer be ignored, as they represent one of our most widespread cultural values. Their narratives connect directly with the way our young people think, feel, and dialogue. Therefore, embracing video games, both culturally and educationally, is a leap forward with an eye to progress.